Leadership (John Wiley & Sons, 2004)
In the new workplace, the old rules of business don’t always apply. That’s why Fast Company magazine has always looked to the organizations and people who are rewriting the rules and reinventing business. Fast Company has quickly become the place to turn for influential voices on the future of business and innovative solutions to real problems. Now you can get the latest thinking on leadership, Fast Company style! Featuring twenty-seven articles, grouped into five topic areas, this Fast Company leadership reader will help you to meet the challenges of leading organizations in today’s fast-paced world.